2016
DOI: 10.1037/rep0000073
|View full text |Cite
|
Sign up to set email alerts
|

Is the intensive care unit traumatic? What we know and don’t know about the intensive care unit and posttraumatic stress responses.

Abstract: The intensive care unit (ICU) has been portrayed as psychologically stressful, with a growing body of research substantiating elevated rates of depression, posttraumatic stress disorder (PTSD), and other psychological disruptions in populations of critical care survivors. To explain these psychopathology elevations, some have proposed a direct effect of ICU admission upon the later development of psychopathology, whereas others highlight the complex interaction between the trauma of a life-threatening illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 92 publications
(139 reference statements)
3
46
2
1
Order By: Relevance
“…One study found that social support was significantly negatively associated with PTSD symptoms in a sample of ICU patients admitted for ARDS. This association in ICU-treated individuals between social support and decreased psychological distress could represent an important topic for future research (87, 93). …”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 94%
See 3 more Smart Citations
“…One study found that social support was significantly negatively associated with PTSD symptoms in a sample of ICU patients admitted for ARDS. This association in ICU-treated individuals between social support and decreased psychological distress could represent an important topic for future research (87, 93). …”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 94%
“…Similarly, Cuthbertson et al found that treatment-seeking behaviors for psychological distress prior to ICU predicted eventual development of PTSD (86). However these studies assessed previous psychiatric history using retrospective accounts, and it could be questioned if the self-reports of previous psychopathology may have been increased by current psychological distress (87). …”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
See 2 more Smart Citations
“…The medical conditions of long-term ICU patients often fluctuate due to complications such as infections and re-intubation. ICU stays beyond 7 days are associated with a high mortality rate (Carden et al, 2008;Moitra et al, 2016) and elevated rates of psychopathology (Kean et al, 2017;McGiffin, Galatzer-Levy, & Bonanno, 2016). In spite of multiple challenges from long-term, life-threatening illnesses, along with medical treatment and nursing interventions, some long-term ICU patients demonstrate an exceptional inner strength (Smith, Dingley, & Roux, 2018) and will to go on living (Alpers, Helseth, & Bergbom, 2012;Engstrøm, Nystrøm, Sundelin, & Rattray, 2013).…”
Section: Introductionmentioning
confidence: 99%